Dual phase zirconium-based metal-organic gel (Zr-MOG) as chromium (VI) removal via photoreduction / Anis Muneerah Shaiful Bahari ... [et al.] - Shaiful Bahari, Anis Muneerah; Alias, Nurhaswani; Rosli, Siti Azlina; Abu Hasan Sazalli, Nurliyana; Lockman, Zainovia; Misran, Halina (Universiti Teknologi MARA Shah Alam, 2023)
Given the widespread production of Cr(VI) from numerous industrial processes, as well as its harmful toxicity as a carcinogenic agent, it is critical to explore stable and efficient adsorbents with quick performance for Cr(VI). Recently, environmentally friendly adsorbents have been employed to reduce metallic pollutants in aqueous media called zirconium-containing metal-organic frameworks (Zr-MOFs) or UiO-66. UiO-66 are favourable because of their nontoxic metal sources, outstanding stabilities, and distinctive physicochemical characteristics. Despite the benefits of using MOFs, overcoming their poor macro-shaping and hydro-stability to be used as commercial adsorbents and catalysts remains a significant problem. Zirconium-based metal-organic gel (Zr-MOG) xerogel is widely known as a new nanomaterial to overcome metal-organic framework (MOFs) disadvantage as microcrystalline powder. This research is an effort to investigate green Zr-MOG as a potential photocatalyst for reducing Cr(VI) to Cr(III) ions. The behaviour of Zr-MOG in dark adsorption and photocatalysis, with and without a scavenger, as well as its reusability were studied. Besides that, synthesised Zr-MOG xerogel exhibited three different X-ray diffraction (XRD) pattern categories: fully amorphous, 1:1 ratio and 1:4 ratio of amorphous and crystalline structure. The performance of pure amorphous MOG, pure crystalline MOG and dual-phase MOG as photocatalysts were compared. The dual-phase structure Zr-MOG 5 exhibits the greatest Cr(VI) ion reduction, with an 87% removal rate in 120 minutes.